Psychometric Studies of the Learning Strategies Scale for University Students - Boruchovitch, Evely; Santos, Acácia Aparecida Angeli dos (Paidéia (Ribeirão Preto), 2015)
The aim of this article is to examine the psychometric properties of a learning strategies scale for university students. The scale was composed of 49 Likert scale items related to cognitive and metacognitive strategies. It was applied in a sample of 1,490 university students. The factor analysis revealed that 35 items had acceptable loadings and identified a three factor structure: Factor 1 - Cognitive and Metacognitive Self-regulation, Factor 2 - Internal Resource and Context regulation, and Factor 3 - Social regulation. Its internal consistency was assessed by Cronbach’s alpha and was .87 for the total scale, .86 for Factor 1, .71 for Factor 2 and .65 for Factor 3. The total variance explained was 26.6%. Further studies are suggested based on confirmatory factor analyses, so that the scale can be better utilized in psychoeducational evaluation.